Compassionate Theodicy: A Suggested Truce Between Intellectual and Practical Theodicy. (15th February 2021) - Sollereder, Bethany N.
Abstract: The basic morality of theodicy is oft disputed. Classical theodicists defend the pursuit of an intellectual solution to the problem of evil while anti‐theodicists and practical theodicists argue that this distracts efforts from alleviating the pain people suffer. In this article, I draw on psychological studies that show that beliefs about God and evil change how resilient people are in their experience of pain. In light of that research, I suggest that the pursuit of an intellectual solution to the problem of evil is actually a part of the practical response to evil. However, the pursuit of a solution must be undertaken by the person who has suffered evil, not by the theodicist on their behalf. The theodicist must instead take up the role of coach or guide to the process of making sense of evil—this is what I call compassionate theodicy. I finish with an example of a resource that attempts a compassionate theodicy, showing the links between theory and practice.